1996
DOI: 10.1016/0304-3959(96)03108-9
|View full text |Cite
|
Sign up to set email alerts
|

Coping with chronic pain: flexible goal adjustment as an interactive buffer against pain-related distress

Abstract: In the present study, Brandtstädter's (1992) distinction between assimilation and accommodation as two fundamental means of coping is applied to the field of chronic pain. Assimilative coping involves active attempts (e.g. instrumental activities, self-corrective actions, compensatory measures) to alter unsatisfactory life circumstances and situational constraints in accordance with personal preferences. Conversely, accommodative coping (e.g. downgrading of aspirations, positive reappraisal, self-enhancing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 41 publications
12
113
1
9
Order By: Relevance
“…Interestingly, it was also positively correlated with acceptance, suggesting that those patients with a higher ability to flexibly adjust unattainable goals are better in accepting their illness. This is not that surprising, given that there is some conceptual overlap between both constructs [20,24,26]. Nevertheless, the overlap is far from complete, and acceptance uniquely explained QOL on top of goal regulation styles.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, it was also positively correlated with acceptance, suggesting that those patients with a higher ability to flexibly adjust unattainable goals are better in accepting their illness. This is not that surprising, given that there is some conceptual overlap between both constructs [20,24,26]. Nevertheless, the overlap is far from complete, and acceptance uniquely explained QOL on top of goal regulation styles.…”
Section: Discussionmentioning
confidence: 98%
“…Wrosch and colleagues [21] found that goal disengagement and goal re-engagement tendencies compensate for the distress associated with the occurrence of unattainable goals. In the chronic pain literature, Schmitz and colleagues [24] found a buffering effect of flexible goal adjustment on the correlation between both pain intensity and disability, and depression. We have no direct explanation for the failure to observe any of the hypothesized moderation effects in this sample of MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmitz, Saile, & Nilges (1996) reported that low Flexible Goal Adjustment interacted with high pain intensity (and disability) to predict high levels of depression. Also, Kranz, Bollinger, & Nilges (2010) reported that high Flexible Goal Adjustment was associated with increased pain willingness and activity engagement (two complementary aspects of chronic pain acceptance) particularly at high average pain intensity levels.…”
Section: Coping and Emotion Regulation -Context-dependence In Chronicmentioning
confidence: 99%
“…Different variables, such as pain (Fifield et al, 1998), negative affect , depression (Schmitz et al, 1996) Third, the models differ in their predictions regarding the intra-or interpersonal level of the relationships they explain. As discussed by Zautra et al (2005), the intrapersonal level answers "when"-questions, while interpersonal differences address "who"-questions.…”
Section: ______________________mentioning
confidence: 99%